Customer Satisfaction Index of Singapore 2017: Q1 Results - Institute of Service Excellence, SMU (Institutional Knowledge at Singapore Management University, 2017)
The Customer Satisfaction Index of Singapore (CSISG) computes customer satisfaction scores at the national, sector, sub-sector, and company levels. The CSISG serves as a quantitative benchmark of the quality of goods and services produced by the Singapore economy over time. 2017 marks the 11th year of measurement for the CSISG national study.